2014
DOI: 10.1177/0883073814553799
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Neurocritical Care Service Is Associated With Decreased Administration of Seizure Medication

Abstract: This cohort study examines medication use in term neonates with hypoxic-ischemic encephalopathy (HIE) and seizures before and after implementation of a Neonatal Neurocritical Care Service (N=108), which included increased seizure monitoring. Nearly all neonates received phenobarbital (96% pre- versus 95% post-Neonatal Neurocritical Care Service) and total loading dose did not vary among groups (33 [95% CI 29–37] versus 30 [26–34] mg/kg). After adjustment for seizure burden, neonates managed during the Neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…However, there is evidence that NeuroNICUs have changed practices and improved care in ways that are likely to impact neurodevelopmental outcomes and may positively impact families by reducing exposure to sedating medications and by reducing length of hospital stay. [30][31][32][33] Bashir et al describe a significant improvement in electrographic seizure detection, lower phenobarbital burden, and less anticonvulsant therapy at discharge associated with a clinical protocol in their neurocritical care program that used cEEG for 72 hours in all babies with HIE. 30 Similar findings were seen in an earlier study by Wietstock et al who reported that implementation of a neonatal neurocritical care service was associated with a reduction in cumulative phenobarbital dose, shorter duration of maintenance dosing, less medication use at discharge, and a shorter length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that NeuroNICUs have changed practices and improved care in ways that are likely to impact neurodevelopmental outcomes and may positively impact families by reducing exposure to sedating medications and by reducing length of hospital stay. [30][31][32][33] Bashir et al describe a significant improvement in electrographic seizure detection, lower phenobarbital burden, and less anticonvulsant therapy at discharge associated with a clinical protocol in their neurocritical care program that used cEEG for 72 hours in all babies with HIE. 30 Similar findings were seen in an earlier study by Wietstock et al who reported that implementation of a neonatal neurocritical care service was associated with a reduction in cumulative phenobarbital dose, shorter duration of maintenance dosing, less medication use at discharge, and a shorter length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Another study similarly concluded that there was no significant change in the number of ASDs prescribed for neonatal seizures after the introduction of aEEG in an NICU compared with the use of serial conventional EEGs [17]. Wietstock et al [15] reported a significant reduction in the cumulative dose of phenobarbital and no change in the number of ASDs used in neonates with HIE-related seizures before and after the implementation of a neonatal neurocritical care service, which included TH treatment, cEEG monitoring, seizure management guidelines, and educating physicians and nurses. None of these studies was limited to neonates undergoing TH as in our study, but rather included either all neonates with suspected seizures who were admitted to an NICU [1517].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the impact of different types of EEG monitoring on clinical care measures such as the number of ASDs used in the management of neonatal seizures [1517]. Ours is the first study to address this outcome solely in neonates with HI-related seizures that were all treated with TH.…”
Section: Introductionmentioning
confidence: 99%
“…The three papers improving outcomes in neonatal status epilepticus report decreased administration of seizure medications with possible adverse effects on neurodevelopment (2224). Bashir’s group and Wiestock’s group specifically focus their implementation strategies on the development of a neonatal neurocritical care team in order to improve recognition and standardize treatment of seizures for patients with hypoxic ischemic encephalopathy.…”
Section: Application Of Implementation Strategies In Pediatric Neurocmentioning
confidence: 99%
“…Bashir’s group and Wiestock’s group specifically focus their implementation strategies on the development of a neonatal neurocritical care team in order to improve recognition and standardize treatment of seizures for patients with hypoxic ischemic encephalopathy. With the use of implementation strategies heavily focused on planning, educating, and restructuring healthcare delivery, these groups were able to significantly decrease the cumulative doses of phenobarbital without needing to prescribe additional or increased doses of other anti-epileptic medicines (22, 24). Haris’ group also used strategies focused on planning and educating, but did not rely as heavily on restructuring healthcare delivery at their institution.…”
Section: Application Of Implementation Strategies In Pediatric Neurocmentioning
confidence: 99%